Composite positive electrode material, positive electrode plate containing composite positive electrode material and lithium ion secondary battery
By using composite positive electrode materials in lithium-ion secondary batteries, combining lithium manganese oxide and nickel-doped lithium manganese oxide and nickel-doped lithium manganese ternary or nickel-cobalt manganese aluminum quaternary materials, the particle size distribution and cladding elements are solved The problem of structural distortion of lithium manganate during charging and discharging has improved the energy density and cycle stability of the battery and enhanced safety performance.
Patent Information
- Application Number
- CN202411484411.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-13
AI Technical Summary
The electrochemical performance, cycle stability and safety performance of existing lithium-ion secondary batteries are poor, especially the structural distortion caused by the Jahn-Teller effect during the charging and discharging process of lithium manganese oxide, resulting in deterioration of battery performance.
Compound positive electrode materials, including lithium manganese oxide and nickel-doped lithium manganese oxide as the first positive electrode materials, nickel-cobalt-manganese ternary or nickel-cobalt-manganese-aluminum quaternary as the second positive electrode materials, and control particle size distribution and cladding elements , optimize the particle size ratio and cladding content, form a suitable particle size distribution and structure, and improve the energy density and cycle life of the battery.
It significantly improves the electrochemical performance, cycle stability and safety performance of the battery, reduces the risk of thermal runaway, extends the cycle life of the battery, and reduces production costs.
Smart Images

Figure CN119133416A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery materials, and in particular to a composite positive electrode material, a positive electrode sheet containing the same, and a lithium-ion secondary battery. Background Art
[0002] Many cathode materials currently on the market, such as lithium cobalt oxide, lithium manganese oxide, ternary materials, and lithium iron phosphate, suffer from varying degrees of deficiencies in energy density, cycle performance, rate capability, high-temperature performance, safety, and cost when used alone. This makes single cathode materials unable to meet the growing demand for multifunctionality in diverse electrical products. Composite cathode materials not only simplify processing but also enhance the advantages of individual materials while mitigating their shortcomings. This significantly reduces production costs for battery companies, offering unique advantages in balancing cost and performance. To achieve a high energy density, manufacturers currently utilize a blend of high-cost lithium cobalt oxide or ternary materials with low-cost lithium manganese oxide to achieve a balance between energy density and cost. This approach involves continuously reducing the amount of lithium cobalt oxide or ternary materials and increasing the proportion of lithium manganese oxide in the blend. Therefore, from a cost and safety perspective, lithium manganese oxide is undoubtedly one of the most suitable options for future power batteries, particularly in consumer electronics, digital electronics, and small power tools, where it plays an irreplaceable role. However, the current capacity and compaction of lithium manganese oxide (LMO) are significantly lower than those of ternary materials. Mixing the two results in lower capacity and compaction of the composite cathode material to varying degrees, especially when the LMO content increases. Furthermore, during the charge and discharge cycle of LMO, the structure of the cathode material is distorted due to the Jan-Taylor effect. All of these factors deteriorate the battery's electrochemical performance, cycle stability, and safety. Summary of the Invention
[0003] The present application provides a composite positive electrode material, a positive electrode plate containing the same, and a lithium-ion secondary battery, which aims to solve the problems of deterioration of electrochemical performance, cycle stability and safety performance of existing lithium-ion secondary batteries to a certain extent.
[0004] In a first aspect, the present application provides a composite positive electrode material, the composite positive electrode material comprising a first positive electrode material and a second positive electrode material, the first positive electrode material comprising one or more of lithium manganese oxide and nickel-doped lithium manganese oxide materials, the second positive electrode material comprising one or more of a nickel-cobalt-manganese ternary positive electrode material and a nickel-cobalt-manganese-aluminum quaternary positive electrode material; 1.35≤Dv1 / Dv2≤14.29;
[0005] Among them, Dv1 = Dv1(100) * Dv1(99) / Dv1(50), Dv2 = Dv2(100) * Dv2(99) / Dv2(50), where Dv1(50), Dv1(99), and Dv1(100) are the particle sizes corresponding to when the cumulative particle size distribution percentage of the first positive electrode material reaches 50%, 99%, and 100% respectively; Dv2(50), Dv2(99), and Dv2(100) are the particle sizes corresponding to when the cumulative particle size distribution percentage of the second positive electrode material reaches 50%, 99%, and 100% respectively.
[0006] In an optional embodiment, 5μm ≤ Dv1(50) ≤ 15μm, 30μm ≤ Dv1(100) ≤ 50μm, 20μm ≤ Dv1(99) ≤ 40μm, 80μm ≤ Dv1 ≤ 230μm.
[0007] In an optional embodiment, 1μm ≤ Dv2(50) ≤ 5.2μm, 5μm ≤ Dv2(100) ≤ 20μm, 5μm ≤ Dv2(99) ≤ 15μm, 15μm ≤ Dv2 ≤ 60μm.
[0008] In an optional embodiment, the first positive electrode material has the following molecular formula: LiMn 2-x Ni x O4, where 0 ≤ x ≤ 0.3; preferably, 0.1 ≤ x ≤ 0.2.
[0009] In an optional embodiment, the second positive electrode material has the following molecular formula: Li(Ni x Co y Mn z Al m )O2, where 0.85 ≤ x < 1, 0 < y < 0.1, 0 < z < 0.1, −0.1 ≤ m < 0.1, x + y + z = 1; preferably, 0.88 ≤ x < 1, 0 < y < 0.05, 0 < z < 0.05, 0 ≤ m < 0.02, x + y + z = 1.
[0010] In an optional embodiment, the mass percentage of the first positive electrode material in the composite positive electrode material is 10% - 90%, and the mass percentage of the second positive electrode material in the composite positive electrode material is 10% - 90%; and / or, the first positive electrode material includes single crystal particles; and / or, the second positive electrode material includes single crystal particles.
[0011] In an optional embodiment, the composite positive electrode material satisfies one or both of the following a - b:
[0012] a. A first coating layer is provided on the surface of the first positive electrode material. The first coating layer includes a first coating element, and the first coating element includes magnesium.
[0013] b. A second coating layer is provided on the surface of the second positive electrode material. The second coating layer includes a second coating element. The second coating element includes at least one of tungsten and strontium.
[0014] In an optional embodiment, the composite cathode material further satisfies the following relationship:
[0015] 0.33≤A / (B+C)≤50;
[0016] Among them, A is the mass content of the first coating element based on the mass of the first positive electrode material; B is the mass content of the tungsten element based on the mass of the second positive electrode material; C is the mass content of the strontium element based on the mass of the second positive electrode material; 0.1%≤A≤1%, 0.01%≤B≤0.2%, 0.01%≤C≤0.1%.
[0017] In an optional embodiment, in the XRD diffraction pattern of the second positive electrode material, the peak intensity I(003) of the crystal plane (003) and the peak intensity I(104) of the crystal plane (104) satisfy: I(003) / I(104)≥1.2;
[0018] And / or, in the XRD diffraction pattern of the second positive electrode material, the peak intensity I(101) of crystal plane (101), the peak intensity I(006) of crystal plane (006) and the peak intensity I(012) of crystal plane (012) satisfy: (I(006)+I(012)) / I(101))≤0.5.
[0019] In a second aspect, the present application provides a positive electrode plate, comprising a current collector and a paste layer disposed on the current collector, wherein the paste layer comprises any composite positive electrode material described in the first aspect of the present application.
[0020] In an optional embodiment, the thickness of the current collector is 8-16 μm, and the thickness of a single side of the pasting layer is 10-100 μm.
[0021] In an optional embodiment, the resistivity of the positive electrode plate is 0.2-5 KΩ·cm, and the surface resistance is 20-600 mΩ.
[0022] In an optional embodiment, the peel strength of the positive electrode sheet is 0.01-0.2 kgf.
[0023] In an optional embodiment, the porosity of the positive electrode sheet is 20%-40%.
[0024] In an optional embodiment, the current collector is aluminum foil.
[0025] In an optional embodiment, the aluminum foil has a tensile strength of ≥150 MPa, a surface roughness of 0.1-1.5 μm, and a thickness of 8-16 μm.
[0026] In a third aspect, the present application provides a lithium-ion secondary battery, comprising the positive electrode sheet described in the second aspect of the present application; and also comprising an electrolyte.
[0027] In an optional embodiment, the electrolyte includes a lithium salt, an organic solvent and an additive.
[0028] In an optional embodiment, the lithium salt includes one or more of lithium hexafluorophosphate (LiFP6), lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB), lithium bis(trifluoromethylsulfonylimide) (LiTFSI), lithium bis(fluorooxalatoborate) (LiODFB), and lithium bis(fluorosulfonylimide) (LiFSI).
[0029] In an optional embodiment, the organic solvent includes one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC).
[0030] In an optional embodiment, the additive includes one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC) and 1,3-propane sultone (1,3-PS).
[0031] The technical solution of this application has the following advantages:
[0032] The composite positive electrode material provided in the present application includes a first positive electrode material, and the composite positive electrode material includes a first positive electrode material and a second positive electrode material, the first positive electrode material includes one or more of lithium manganese oxide and nickel-doped lithium manganese oxide materials, and the second positive electrode material includes one or more of nickel-cobalt-manganese ternary positive electrode materials and nickel-cobalt-manganese-aluminum quaternary positive electrode materials; the composite positive electrode material satisfies the following relationship: 1.35≤Dv1 / Dv2≤14.29; by regulating the Dv1 and Dv2 series particle size parameters and their mutual relationship, the high energy density, long cycle life and good safety performance of the battery material are achieved.
[0033] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the following is a brief introduction to the drawings required for use in the specific implementation methods or the description of the prior art. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0035] Figure 1 1 is the discharge curve of the battery of Example B1 and Comparative Examples B1 and B2 in the test examples of this application;
[0036] Figure 2 These are the cycle performance curves of the batteries of Example B1 and Comparative Examples B1 and B2 in the test examples of this application. DETAILED DESCRIPTION
[0037] The following examples are provided to further better understand the present application, but are not limited to the best implementation mode described herein, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the scope of protection of the present application.
[0038] In the description of this application, it should be noted that the terms "inner" and "outer" and the like, indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings and are intended solely to facilitate the description of this application and simplify the description. They are not intended to indicate or imply that the devices or components referred to must have a specific orientation, be constructed, or operate in a specific orientation. Therefore, they should not be construed as limitations on this application. Furthermore, the terms "first," "second," and "third" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.
[0039] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in this field can be used. If the manufacturer of the reagents or instruments is not specified, they are all commercially available conventional reagents.
[0040] In addition, the technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0041] This application provides a composite positive electrode material, a positive electrode sheet containing the same, and a lithium-ion secondary battery, which can increase the capacity and compactness of the composite positive electrode while significantly improving the electrochemical performance, cycle stability, and safety of the battery. The technical solution adopted in this application is described below.
[0042] In a first aspect, the present application provides a composite positive electrode material, wherein the composite positive electrode material comprises a first positive electrode material and a second positive electrode material, wherein the first positive electrode material comprises one or more of lithium manganese oxide and nickel-doped lithium manganese oxide materials, and the second positive electrode material comprises one or more of nickel-cobalt-manganese ternary positive electrode materials and nickel-cobalt-manganese-aluminum quaternary positive electrode materials; the composite positive electrode material satisfies the following relationship: 1.35≤Dv1 / Dv2≤14.29; wherein Dv1=Dv1(100)*Dv1(99 ) / Dv1(50), Dv2=Dv2(100)*Dv2(99) / Dv2(50), Dv1(50), Dv1(99), Dv1(100) are the particle sizes corresponding to the cumulative particle size distribution percentages of the first positive electrode material reaching 50%, 99%, and 100%, respectively; Dv2(50), Dv2(99), Dv2(100) are the particle sizes corresponding to the cumulative particle size distribution percentages of the second positive electrode material reaching 50%, 99%, and 100%, respectively.
[0043] In the present application, the first positive electrode material, which includes one or more of lithium manganese oxide and nickel-doped lithium manganese oxide materials, has excellent thermal stability and is not prone to decomposition and thermal runaway, but has poor cycle performance; while the second positive electrode material, which includes one or more of nickel-cobalt-manganese ternary positive electrode materials and nickel-cobalt-manganese-aluminum quaternary positive electrode materials, has poor thermal stability but excellent cycle performance. The composite positive electrode material of the present application includes the above-mentioned first positive electrode material and the second positive electrode material. By strictly controlling the particle size ratio and distribution of the two materials, the battery material has high energy density, long cycle life and good safety performance.
[0044] If the ratio of Dv1 to Dv2 is too large, it indicates that the particle size distribution is wide, and the particle size difference between the large particles of the first positive electrode material and the small particles of the second positive electrode material is too large. This will lead to insufficient packing of particles during the compaction process, reduced compaction density of the pole piece, reduced energy density of the battery, and uneven electrolyte penetration. The charging and discharging capabilities of different positions of the battery vary greatly, resulting in uneven electrochemical reactions of the battery and poor battery cycle performance. In addition, due to the large difference in particle size, local overheating will occur during the furnace temperature and overcharge tests of the battery. There is a large difference in heat accumulation between large particles and small particles. When the temperature reaches a certain level, the thermal decomposition reaction of the second positive electrode material is triggered, generating a large amount of heat and gas, increasing the risk of thermal runaway of the battery.
[0045] If the ratio of Dv1 to Dv2 is too small, the particle size distribution is too concentrated, and there are not enough small particles to fill the gaps between large particles, which will also have an adverse effect on the stacking efficiency, resulting in a decrease in the battery energy density. The particle size distribution is too concentrated, which will also cause the second positive electrode material to have a larger volume change during lithium insertion and extraction. The large volume change will cause a relatively large stress between the particles, which will destroy the structure of the positive electrode material as the cycle progresses, reducing the cycle performance of the battery. In addition, if the particle size of the two materials decreases simultaneously, the specific surface area of the material will increase significantly. The increase in specific surface area increases the contact area between the positive electrode material and the electrolyte, accelerates the side reactions between the positive electrode material and the electrolyte, and quickly produces gas and heat, causing thermal runaway of the battery. If the particle size of the two materials increases simultaneously, it will hinder heat dissipation, and heat will also accumulate inside the battery, increasing the risk of thermal runaway of the battery.
[0046] In addition, if the above-mentioned particle size ratio is too large or too small, it will also affect the fluidity of the material. If the ratio of Dv1 to Dv2 is too small, too many large particles will easily cause the material to clog the coating head or be difficult to distribute evenly. If the ratio of Dv1 to Dv2 is too large, the small particles of the second positive electrode material will account for too much of the large particles of the first positive electrode material, making the material too loose and difficult to maintain a stable flow state, resulting in uneven coating of the material on the electrode sheet, which will also lead to poor cycle performance. When the composite positive electrode material satisfies the above-mentioned particle size distribution relationship (the ratio of Dv1 to Dv2 is between 1.35 and 14.29), the heat distribution inside the battery is optimized, the occurrence of local overheating is suppressed, and the furnace temperature performance of the composite positive electrode material is improved. By optimizing the particle size distribution and ratio, the composite positive electrode material also improves the transmission kinetics of lithium ions, so that lithium ions can be more evenly embedded in and out of the surface of the negative electrode material during the charge and discharge process, reducing the uneven deposition of lithium metal, i.e., the occurrence of lithium plating.
[0047] In summary, by regulating the Dv1 and Dv2 series particle size parameters and their mutual relationship, high energy density, long cycle life and good safety performance of battery materials can be achieved. As an example, Dv1 / Dv2 can be 1.35, 3, 5, 8, 14.29 or within the range of any two of the above values. Dv1(50), Dv1(99), Dv1(100) of the first positive electrode material and Dv2(50), Dv2(99), Dv2(100) of the second positive electrode material are all measured by laser particle size analyzer. Specifically, ultrapure water is selected as the dispersion medium, 1g of the first positive electrode material sample or the second positive electrode material sample is added to 1L of the dispersion medium, and ultrasonicated for 60min to fully disperse the sample to form a uniform suspension or dispersion. The prepared sample suspension or dispersion is poured into the sample cell, and the laser particle size analyzer is turned on for testing. After the test is completed, the computer will generate a particle size distribution diagram and related data report.
[0048] In an optional embodiment, 5μm≤Dv1(50)≤15μm, 30μm≤Dv1(100)≤50μm, 20μm≤Dv1(99)≤40μm, and 80μm≤Dv1≤230μm. As an example, Dv1(50) can be 5μm, 8μm, 10μm, 15μm, or within a range consisting of any two of the above values. As an example, Dv1(100) can be 30μm, 35μm, 40μm, 45μm, 50μm, or within a range consisting of any two of the above values. As an example, Dv1(99) can be 20μm, 25μm, 30μm, 40μm, or within a range consisting of any two of the above values. Dv1 can be 80μm, 100μm, 150μm, 200μm, 230μm, or within a range consisting of any two of the above values.
[0049] In an optional embodiment, 1 μm ≤ Dv2 (50) ≤ 5.2 μm, 5 μm ≤ Dv2 (100) ≤ 20 μm, 5 μm ≤ Dv2 (99) ≤ 15 μm, and 15 μm ≤ Dv2 ≤ 60 μm. As an example, Dv2 (50) can be 1 μm, 2 μm, 4 μm, 5.2 μm, or within a range consisting of any two of the above values. As an example, Dv2 (100) can be 5 μm, 10 μm, 15 μm, 20 μm, or within a range consisting of any two of the above values. As an example, Dv2 (99) can be 5 μm, 8 μm, 10 μm, 15 μm, or within a range consisting of any two of the above values. Dv2 can be 15 μm, 20 μm, 30 μm, 45 μm, 60 μm, or within a range consisting of any two of the above values.
[0050] In an optional embodiment, the first cathode material has the following molecular formula: LiMn 2-x Ni xO4, where 0 ≤ x ≤ 0.3; preferably, 0.1 ≤ x ≤ 0.2. Through the above-mentioned first positive electrode material, not only the cost can be reduced and the efficiency can be increased, but also the safety can be improved, and the overcharge safety performance and rate performance of the battery can be enhanced. As an example, x can be 0, 0.1, 0.2, 0.3 or within the range composed of any two of the above values. When using nickel-doped lithium manganese oxide material, especially when controlling 0.1 ≤ x ≤ 0.2, the main functions are as follows: ① Improve the electrochemical capacity. Nickel has a higher chemical valence, and each nickel atom can provide more lithium ion storage positions, which can increase the electrochemical capacity of the lithium manganese oxide material; ② Improve the cycle life and stability of the battery. During the cycle process of the lithium manganese oxide material, structural damage and manganese dissolution problems may occur, resulting in a decline in battery performance. The addition of nickel can improve the structural stability of the material and the cycle life of the battery, reduce the dissolution rate of the material, and thus improve the cycle stability of the battery; ③ Optimize the power performance of the battery. The conductivity of pure lithium manganese oxide is relatively low, which limits its performance in high-power applications. The incorporation of nickel elements can improve the conductivity and ion diffusion performance of the material, and increase the charge-discharge rate and power density of the battery. ④ Inhibit the dissolution of manganese. The addition of nickel can slow down the dissolution rate of manganese ions in the lithium manganese oxide material because the crystal structure and chemical properties of nickel can improve the compatibility between the positive electrode material and the electrolyte, reducing unnecessary chemical reactions and dissolution paths; In short, by blending nickel elements, some defects of the lithium manganese oxide material can be compensated to a certain extent, improving its electrochemical performance and cycle stability, so that the lithium-ion battery can exhibit more excellent performance in terms of energy density, power density and cycle life. As an example, x can be 0.1, 0.2, 0.3 or within the range composed of any two of the above values.
[0051] In an optional embodiment, the second positive electrode material has the following molecular formula: Li(Ni x Co y Mn z Al m )O2, where 0.85 ≤ x < 1, 0 < y < 0.1, 0 < z < 0.1, 0 ≤ m < 0.1, and x + y + z + m = 1. As an example, x can be 0.85, 0.90, 0.92, 0.94, 0.96, 0.98, 0.99 or within the range composed of any two of the above values. As an example, y can be 0.02, 0.04, 0.06, 0.08 or within the range composed of any two of the above values. As an example, z can be 0.02, 0.04, 0.06, 0.08 or within the range composed of any two of the above values. As an example, m can be 0, 0.005, 0.01, 0.02, 0.04, 0.06, 0.08 or within the range composed of any two of the above values.
[0052] In an alternative embodiment, 0.88 ≤ x < 1, 0 < y < 0.05, 0 < z < 0.05, 0 ≤ m < 0.02, and x + y + z + m = 1. Given that the specific capacity per gram of the first cathode material is relatively low, while the high-nickel ternary material of the second cathode material exhibits a significant advantage of high specific capacity, the ternary material with an ultra-high nickel content is specifically selected for blending in the present invention to ensure the energy density of the battery and compensate for the insufficient specific capacity of the first cathode material. Specifically, the nickel content x is strictly controlled within the range of 0.88 ≤ x < 1 to maximize the specific capacity. At the same time, in order to effectively reduce the cost of the ternary material, the present invention reduces the usage amount of cobalt, controls the cobalt content y within the relatively low range of 0 < y < 0.05, and the manganese content z is maintained within the range of 0 < z < 0.05 to maintain the stability and structural integrity of the material. The aluminum content m is maintained within the range of 0 ≤ m < 0.02 to improve the thermal stability performance of the material. As an example, x can be 0.88, 0.90, 0.92, 0.94, 0.96, 0.98, 0.99 or within the range composed of any two of the above values. As an example, y can be 0.02, 0.04, 0.045 or within the range composed of any two of the above values. As an example, z can be 0.02, 0.04, 0.045 or within the range composed of any two of the above values. As an example, m can be 0, 0.005, 0.01, 0.15 or within the range composed of any two of the above values.
[0053] In an alternative embodiment, the mass percentage of the first cathode material in the composite cathode material is 10% - 90%, and the mass percentage of the second cathode material in the composite cathode material is 10% - 90%. The first cathode material has a lower cost relative to the second cathode material. A reasonable ratio helps to reduce the overall battery cost. At the same time, the first cathode material has higher thermal stability than the second cathode material. The incorporation of the first cathode material can improve the furnace temperature and overcharge safety of the battery. Controlling the mass ratio of the first cathode material and the second cathode material within the above range can better achieve the effect of reducing costs and increasing efficiency while improving the battery safety, enhancing the overcharge safety performance and rate performance of the battery. As an example, the mass percentage of the first cathode material is 10%, 30%, 50%, 70%, 90% or within the range composed of any two of the above values, and the mass percentage of the second cathode material is 10%, 30%, 50%, 70%, 90% or within the range composed of any two of the above values.
[0054] In an alternative embodiment, the first cathode material includes single crystal particles. For single crystal lithium manganate particles, due to no grain boundaries or particle gaps inside, the crystal structure is orderly and compact. This structure enables the single crystal particles to pack more closely during compaction, forming a higher compaction density.
[0055] In an optional embodiment, the second cathode material comprises single crystal particles. Single crystal particles of the second cathode material have an ordered and compact crystal structure due to the absence of grain boundaries or intergranular gaps. This structure enables the single crystal particles to be packed more densely during compaction, resulting in a higher compaction density.
[0056] In an optional embodiment, a first coating layer is provided on the surface of the first positive electrode material, the first coating layer including a first coating element, wherein the first coating element includes magnesium. The coating with magnesium can improve the electrochemical performance of lithium manganese oxide as a positive electrode material, specifically by: 1) improving the electrochemical performance, increasing the material's electrical conductivity and ion transport rate, thereby increasing the battery's charge and discharge efficiency and cycle life; and 2) reducing structural defects in the material, such as lattice vacancies or surface defects, which can affect its electrochemical performance. The coating of magnesium elements can fill some lattice vacancies or reduce surface defects, which helps to improve the stability and cycle performance of the material; ③ Inhibit the dissolution of the material. The coating of magnesium elements can effectively protect the lithium manganese oxide particles to reduce contact with the electrolyte, inhibit the Jahn-Teller distortion ability, and reduce the dissolution of manganese, thereby enhancing the structural stability of the positive electrode material; ④ Optimize the surface reaction of the material. The addition of magnesium elements can change the chemical properties of the lithium manganese oxide surface, making it more compatible with the interface between the electrolyte, thereby reducing the interface resistance and the internal resistance of the battery, and improving the energy density and power density of the battery; In summary, through the coating of magnesium elements, the electrochemical properties and cycle stability of the lithium manganese oxide material can be effectively improved, and its overall performance as a battery positive electrode material can be enhanced.
[0057] In an optional embodiment, based on the molar amount of the first positive electrode material, the molar content of the first coating element is 0.1% to 5%. Controlling the molar content of the first coating element within the above range can better improve the electrochemical performance and cycle stability of the lithium manganese oxide material. As an example, the mass percentage is 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, or within the range of any two of the above values.
[0058] In an optional embodiment, a second coating layer is provided on the surface of the second positive electrode material, and the second coating layer includes a second coating element, wherein the second coating element includes at least one of tungsten and strontium. The addition of these two elements has the following effects: 1. Improving electrochemical performance. The addition of tungsten can improve the conductivity and stability of the material. Tungsten generally has good conductivity and chemical stability, which can improve the electron transfer efficiency of the material, thereby increasing the charge and discharge rate and energy density of the battery; the introduction of strontium can optimize the crystal structure and ion transport path of the material. Strontium generally affects the lattice parameters and crystal structure stability of the material, helping to reduce the phase change and structural degradation of the material, thereby improving the cycle life and stability of the battery; 2. Inhibiting the dissolution of the material and improving the cycle performance. The coating of tungsten and strontium can effectively reduce the dissolution rate of the second positive electrode material in lithium-ion batteries. Dissolution is one of the main reasons for battery capacity loss and reduced cycle life. The introduction of tungsten and strontium can effectively inhibit this process and improve the long-term stability and cycle performance of the battery; ③ Optimize the interface and enhance compatibility with the electrolyte. Surface coating of tungsten and strontium elements can improve the interfacial reactivity and compatibility between the material and the electrolyte. This helps to reduce interfacial resistance and increase the energy density and power density of the battery; ④ Improve the mechanical strength and thermal stability of the material. Tungsten usually has good mechanical strength and thermal stability, which can improve the stability and safety of the material under high temperature and high current conditions. Overall, the surface coating of tungsten and strontium elements can significantly improve the electrochemical performance, cycle life and stability of the second cathode material. It is especially suitable for use in 9-series high-nickel second cathode materials. Due to the increase in nickel proportion, the mixing of nickel and lithium ions in this material is aggravated, and the mixing is in the Li layer, which hinders the diffusion of lithium ions.
[0059] The applicant has discovered that controlling the molar content of the second coating element in the second coating layer to 0.1% to 5%, particularly 1% to 2%, based on the molar amount of the second cathode material, can further improve the electrochemical performance, cycle life, and stability of the second cathode material. For example, the molar content is 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, or any range consisting of any two of these values.
[0060] In an optional embodiment, the composite cathode material further satisfies the following relationship:
[0061] 0.33≤A / (B+C)≤50;
[0062] Where A is the mass content of the first coating element based on the mass of the first positive electrode material; B is the mass content of the tungsten element based on the mass of the second positive electrode material; and C is the mass content of the strontium element based on the mass of the second positive electrode material. 0.1% ≤ A ≤ 1%, 0.01% ≤ B ≤ 0.2%, and 0.01% ≤ C ≤ 0.1%. Research has found that controlling the ratio of A to (B+C) within an appropriate range helps the composite positive electrode material achieve both good structural stability and thermal stability. Secondary positive electrode materials, including one or more of nickel-cobalt-manganese ternary positive electrode materials or nickel-cobalt-manganese-aluminum quaternary positive electrode materials, typically have good cycling performance but poor thermal stability, while first positive electrode materials, including one or more of lithium manganese oxide and nickel-doped lithium manganese oxide materials, have good thermal stability but poor cycling performance. By adjusting A / (B+C) within the above range, the composite positive electrode material can achieve both excellent cycling performance and thermal stability. The magnesium element in the coating layer exists in the form of magnesium oxide, which has high thermal stability and can effectively improve the structural stability of the first positive electrode material and enhance the cycle performance of the battery. If A / (B+C) is too small, the total amount of magnesium element coated in the first positive electrode material becomes lower than the total amount of tungsten element and strontium element coated in the second positive electrode material, and the coating thickness of the second positive electrode material increases relative to the first positive electrode material, resulting in the coating layer in the first positive electrode material being unable to effectively play a role in improving the structural stability during the cycle. At the same time, the volume change of the second positive electrode material during lithium insertion and deintercalation increases, generating greater internal stress during the charge and discharge cycle, resulting in structural damage inside the positive electrode material, affecting the structural stability of the material, and thereby reducing the cycle performance of the battery, which is not conducive to the cycle performance of the battery. If A / (B+C) is too large, it means that the mass of the magnesium element coated in the first positive electrode material is too large compared to the tungsten element and strontium element coated in the second positive electrode material. Instead, a thicker insulating layer will be formed on the surface of the first positive electrode material, which will hinder the transmission path of lithium ions and electrons, resulting in a decrease in the conductivity of the composite positive electrode material. Similarly, the tungsten element and strontium element coated in the second positive electrode material exist in the form of tungsten oxide and strontium oxide. When the tungsten element and strontium element are too little, the thermal stability of the ternary material will deteriorate, making the composite positive electrode material prone to thermal runaway. Therefore, when the above relationship is met, it helps to improve the cycle stability and thermal stability of the battery, reduce the risk of thermal runaway of the battery under high temperature conditions, and improve the furnace temperature and overcharge safety of the battery. As an example, A is 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1% or is within the range of any two of the above values. As an example, B is 0.01%, 0.05%, 0.09%, 0.12%, 0.15%, 0.2%, or a range between any two of the above values. As an example, C is 0.01%, 0.03%, 0.05%, 0.07%, 0.09%, 0.1%, or a range between any two of the above values.The mass content A of the first coating element in the first positive electrode material is determined by inductively coupled plasma emission spectrometry (ICP). The mass content B of the tungsten element in the second positive electrode material; the mass content C of the strontium element are determined by inductively coupled plasma emission spectrometry. Specifically, the first positive electrode material or the second positive electrode material is placed in a mixed solution of hydrochloric acid and nitric acid for digestion for 4 hours to ensure that both the coating layer and the matrix material can be dissolved, and the pretreated solution is introduced into an ICP mass spectrometer. ICP ionizes the atoms or ions in the solution at high temperature, and uses a mass spectrometer to analyze the mass-to-charge ratio of these ions to determine the content of specific elements in the sample. In ICP analysis, the detection parameters are set according to the specific elements contained in the coating layer (such as coating elements, coating materials, etc.), and the concentrations of these elements are measured. Based on the results of the ICP measurement and combined with the sample pretreatment steps, the true content of the elements contained in the coating layer in the original sample is calculated.
[0063] In an optional embodiment, in the XRD diffraction pattern of the second positive electrode material, the peak intensity I(003) of the crystal plane (003) and the peak intensity I(104) of the crystal plane (104) satisfy the following relationship: I(003) / I(104) ≥ 1.2; in this case, the degree of lithium-nickel intermixing in the material is small, and the electrochemical performance of the material is better. As an example, I(003) / I(104) can be 1.5, 3, 5, or within a range consisting of any two of the above values.
[0064] In an optional embodiment, in the XRD diffraction pattern of the second positive electrode material, the peak intensity I(101) of the crystal plane (101), the peak intensity I(006) of the crystal plane (006), and the peak intensity I(012) of the crystal plane (012) satisfy: (I(006)+I(012)) / I(101))≤0.5. At this time, the order of the material is high and the electrochemical performance of the material is excellent. As an example, (I(006)+I(012)) / I(101)) can be 0.03, 0.08, 0.15, 0.3, 0.5, or within the range of any two of the above values.
[0065] In an optional embodiment, the first cathode material is prepared primarily by a high-temperature solid-phase method and involves raw material preparation, mixing, calcination, grinding, and classification. The raw materials include a manganese source and a lithium source. The manganese source can be one or more of manganese oxides, hydroxides, carbonates, and nitrates. The lithium source can be one or more of lithium oxides, hydroxides, carbonates, and nitrates.
[0066] In an optional embodiment, the raw material further includes a nickel source, which may be one or more of nickel oxides, hydroxides, carbonates, and nitrates.
[0067] In an optional embodiment, the calcination temperature is 750° C.-850° C., and the calcination time is 2-8 hours. For example, the calcination temperature is 750° C., 780° C., 800° C., or 850° C., and the calcination time is 2 hours, 4 hours, or 8 hours.
[0068] Calcination under an inert atmosphere. The use of an inert atmosphere is crucial for the synthesis of the first positive electrode material because it helps to improve the lithium storage performance of the first positive electrode material. In addition, the use of an inert atmosphere can also help prevent lithium manganese oxide from being oxidized during the synthesis process, thereby maintaining its purity and excellent crystalline phase, which is crucial for improving the electrochemical properties of lithium manganese oxide. Therefore, the selection and use of an inert atmosphere is an important link in the synthesis process of lithium manganese oxide. It can not only improve the lithium storage performance of the material, but also ensure the purity and crystallinity of the material, thereby optimizing its overall performance. The inert atmosphere can be gases such as argon and helium.
[0069] In an optional embodiment, the second positive electrode material can be prepared by first using a nickel source, a cobalt source, a manganese source and a lithium source, or first using a nickel source, a cobalt source, a manganese source, an aluminum source and a lithium source to obtain a precursor, mixing it with tungsten oxide and strontium oxide, and then calcining it. The calcined product is then ground and classified to obtain the obtained product. The nickel source can be one or more of nickel oxide, hydroxide, carbonate, and nitrate; the cobalt source can be one or more of cobalt oxide, hydroxide, carbonate, and nitrate; the manganese source can be one or more of manganese oxide, hydroxide, carbonate, and nitrate; the aluminum source can be one or more of aluminum oxide, hydroxide, carbonate, and nitrate; and the lithium source can be one or more of lithium oxide, hydroxide, carbonate, and nitrate.
[0070] In an optional embodiment, the coated precursor is calcined at a high temperature (usually greater than 700°C) to cause a solid-phase reaction in the precursor to form a second positive electrode material with a layered structure, and tungsten oxide and strontium oxide are retained on the surface of the material as a coating layer.
[0071] In an optional embodiment, parameters such as atmosphere (such as oxygen, inert gas, etc.), temperature, time and heating rate need to be controlled during the calcination process to ensure the crystal structure and coating effect of the material.
[0072] In an alternative embodiment, the heating rate is 1-5°C / min. The calcination temperature is 700°C-850°C. The calcination time is 8-16 hours. Calcination is performed under an oxygen atmosphere. For example, the heating rate is 1°C / min, 3°C / min, or 5°C / min. The calcination temperatures are 700°C, 780°C, 800°C, or 850°C, and the calcination time is 8 hours, 10 hours, 12 hours, or 16 hours.
[0073] In an alternative embodiment, the calcined product is ground to reduce the particle size and promote uniform distribution of the coating layer. In an alternative embodiment, the ground product is classified to obtain a second positive electrode material having a desired particle size distribution and coated with tungsten oxide and strontium oxide.
[0074] In a second aspect, the present application provides a positive electrode plate, comprising a current collector and a paste layer disposed on the current collector, wherein the paste layer comprises any composite positive electrode material described in the first aspect of the present application.
[0075] In an optional embodiment, the thickness of the current collector is 8-16 μm, and the thickness of the single side of the paste layer is 10-100 μm. The positive electrode sheet set in this way can not only meet the volume energy density of the battery cell, but also the positive electrode active material and the conductive agent of the positive electrode sheet within this thickness range can form a tight three-dimensional conductive network, improve the electronic conductivity of the positive electrode side, make the capacity of the positive electrode material more fully utilized, and the lithium ions are continuously deintercalated during the cycle, and the deterioration of the conductivity between the materials caused by volume expansion can also be alleviated to a certain extent, thereby improving the cycle performance of the battery; in addition, the positive electrode current collector within this thickness range can be in close contact with the paste layer, reducing the contact impedance between the electrode material and the current collector, reducing the polarization of the battery during charging and discharging, thereby improving the power performance of the battery. As an example, the thickness of the current collector is 8 μm, 10 μm, 12 μm, 16 μm or within the range of any two of the above values. The thickness of a single side of the paste layer is 10 μm, 30 μm, 50 μm, 70 μm, 100 μm, or within a range formed by any two of the above values.
[0076] In an optional embodiment, the resistivity of the positive electrode sheet is 0.2-5KΩ·cm, and the surface resistance is 20-600mΩ. When the resistivity and the membrane surface resistance are within this range, the uniformity of the electrode microstructure is good, which is manifested in the close adhesion between the current collector and the paste layer, the uniform distribution of the conductive agent, and the close contact between the active material particles and between the active material and the conductive agent particles, thereby improving the dynamics of the positive electrode sheet, improving the deintercalation ability of lithium ions, improving the lithium precipitation window of the battery, and improving the rate discharge performance of the battery. As an example, the resistivity is 0.2KΩ·cm, 1KΩ·cm, 3KΩ·cm, 5KΩ·cm, or within the range of any two of the above values. The surface resistance is 20mΩ, 100mΩ, 300mΩ, 600mΩ, or within the range of any two of the above values.
[0077] In an optional embodiment, the peel strength of the positive electrode sheet is 0.01-0.2kgf. Due to the continuous deintercalation of lithium ions during long cycles, the internal resistance of the battery increases, current transmission becomes difficult, and insufficient adhesion leads to a decrease in the long cycle performance of the battery. In severe cases, it may even cause the separation of the electrode sheet and the current collector, ultimately leading to battery failure. By limiting the peel strength of the positive electrode sheet to 0.01-0.2kgf, the adhesion between the paste layer and the current collector is still strong in the later stage of the cycle, thereby ensuring the electrical connection between the paste layer and the current collector, more effectively transmitting current, and improving the performance and life of the battery. As an example, the peel strength of the positive electrode sheet is 0.01kgf, 0.05kgf, 0.1kgf, 0.2kgf, or within the range of any two of the above values.
[0078] In an optional embodiment, the porosity of the positive electrode sheet is 20%-40%. This facilitates electrolyte infiltration, improves the ionic conductivity of the positive electrode sheet, reduces the internal resistance of the battery, and improves the rate performance and cycle performance of the battery. As an example, the porosity is 20%, 30%, 40%, or a range consisting of any two of these values.
[0079] In an optional embodiment, the current collector is aluminum foil. As the current collector of the positive electrode sheet, aluminum foil needs to have good electrical conductivity in order to transport electrons from the positive electrode material of the battery to the external circuit. High tensile strength and low roughness can help improve the electrical conductivity of the aluminum foil, thereby reducing the resistance inside the battery and reducing energy loss. In addition, low surface roughness can reduce local poor contact or microscopic gaps between the positive electrode active material and the aluminum foil, thereby reducing the possibility of surface side reactions. When the battery is in the charge and discharge cycle, this poor contact or gap may cause the local current density to increase, causing more surface side reactions to occur in these areas, such as oxidation and reduction of the electrode material, thereby affecting the performance and cycle stability of the battery. The tensile strength of the aluminum foil directly affects the structural stability of the battery. During the charge and discharge cycle of the battery, the electrode active material will expand and contract in volume. If the tensile strength of the aluminum foil is insufficient, it is easy to deform, break or tear, resulting in damage to the internal structure of the battery, thereby affecting the performance and safety of the battery. In order to ensure the performance and safety of the battery, the tensile strength of the aluminum foil is ≥150Mpa (for example, 150-800Mpa), the surface roughness is 0.1-1.5μm, and the thickness of the aluminum foil is 8-16μm. The positive electrode sheet prepared using the aluminum foil current collector meeting the above conditions can effectively and evenly coat and distribute the positive electrode active material, reduce the uneven accumulation of the active material and local thickness differences, thereby improving the structural stability of the electrode, reducing the risk of stress concentration and structural damage caused by material expansion during the charge and discharge cycle, extending the cycle life of the battery, and reducing problems such as increased internal voids in the battery and peeling of electrode active materials due to deformation of the aluminum foil, thereby improving the energy density and cycle performance of the battery. As an example, the tensile strength of the aluminum foil is 150 MPa, 200 MPa, 5000 MPa, 800 MPa or within the range formed by any two of the above values, the surface roughness is 0.1 μm, 0.5 μm, 1 μm, 1.5 μm or within the range formed by any two of the above values, and the thickness of the aluminum foil is 8 μm, 10 μm, 12 μm, 16 μm or within the range formed by any two of the above values.
[0080] In a third aspect, the present application provides a lithium-ion secondary battery, comprising the positive electrode sheet described in the second aspect of the present application; and further comprising an electrolyte, preferably, the electrolyte comprising a lithium salt, an organic solvent, and an additive;
[0081] In an optional embodiment, based on the mass of the electrolyte, the volume proportion of the organic solvent is 90-99%, and the volume proportion of the additive is 1-10%. In an optional embodiment, the concentration of the lithium salt in the electrolyte is 0.8-1.5 mol / L.
[0082] In an optional embodiment, the lithium salt includes one or more of lithium hexafluorophosphate (LiFP6), lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB), lithium bis(trifluoromethylsulfonylimide) (LiTFSI), lithium bis(fluorooxalatoborate) (LiODFB), and lithium bis(fluorosulfonylimide) (LiFSI);
[0083] In an optional embodiment, the organic solvent includes one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC);
[0084] To ensure the film formation stability of the battery material, in an optional embodiment, the additive includes one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC) and 1,3-propane sultone (1,3-PS).
[0085] The material and shape of the separator used in the lithium ion secondary battery of the present application are not particularly limited, and may include any technology disclosed in the prior art.
[0086] The electrolyte used in the lithium-ion secondary battery of the present application may include any electrolyte disclosed in the prior art.
[0087] The present application is further described in detail below with reference to specific examples, which should not be construed as limiting the scope of protection claimed in the present application. In all examples and comparative examples of the present application, the unit wt% represents the percentage by mass.
[0088] Example A1
[0089] The method for preparing the composite positive electrode material provided in this embodiment includes the following steps:
[0090] (1) First positive electrode material
[0091] The first positive electrode material includes a molecular formula of LiMn 1.8 Ni 0.2 The nickel-doped lithium manganate material of O4 also includes a first coating layer, and the first coating layer includes magnesium oxide, and the preparation method thereof is as follows:
[0092] High-purity manganese dioxide, nickel oxide and a lithium source (lithium hydroxide) are weighed according to the element molar ratio of Mn:Ni=9:1 and the element molar ratio of Li:(Mn+Ni)=1:1, and magnesium oxide is precisely weighed according to the mass content of magnesium element in the first positive electrode material being 0.5%. After mixing the raw materials, they are calcined in an inert atmosphere (argon) at a calcination temperature of 850°C for 4 hours. During the calcination process, the raw materials will undergo a solid-phase reaction to form a first positive electrode material, and magnesium oxide will be coated on the surface of the lithium manganate particles; the calcined product is ground (rotation speed 400r / min, time 120min) and graded (passed through a 400-mesh sieve) to obtain the first positive electrode material with the desired particle size distribution.
[0093] (2) Second positive electrode material
[0094] The second positive electrode material includes a molecular formula of Li(Ni 0.92 Co 0.04 Mn 0.04 )O2 nickel-cobalt-manganese ternary positive electrode material, further comprising a second coating layer disposed on the surface of the nickel-cobalt-manganese ternary positive electrode material, the second coating layer comprising tungsten oxide and strontium oxide, and the preparation method thereof is as follows:
[0095] A nickel source (nickel oxide), a cobalt source (cobalt oxide), and a manganese source (manganese dioxide) were weighed at a molar ratio of Ni:Co:Mn = 92:4:4, and a lithium source (lithium hydroxide) was weighed at a molar ratio of Li:(Mn+Co+Ni) = 1:1. These materials were then mixed uniformly to form a nickel-cobalt-manganese-lithium precursor. High-purity tungsten oxide and strontium oxide powders were precisely weighed so that the mass content of tungsten and strontium in the second cathode material was 0.1% and 0.05%, respectively. The high-purity tungsten oxide and strontium oxide powders were then uniformly mixed with the precursor. The mixture was heated to 750°C at a heating rate of 2°C / min in an oxygen atmosphere, held at this temperature for 12 hours, and calcined. The calcined product was ground (in a ball mill at 400 rpm for 120 minutes) and graded (through an 800-mesh screen) to obtain the second cathode material with the desired particle size distribution.
[0096] (3) Preparation of composite cathode materials
[0097] The second positive electrode material and the first positive electrode material were weighed and evenly mixed according to a mass ratio of the second positive electrode material to the first positive electrode material of 85:15 to obtain a composite positive electrode material.
[0098] The preparation method of the composite positive electrode material in Example A2 is basically the same as that in Example A1, except that the calcination temperature in the preparation process of the first positive electrode material is adjusted to 750° C., resulting in different particle size parameters of the first positive electrode material, as shown in Table 1 for details.
[0099] The preparation method of the composite positive electrode material in Example A3 is basically the same as that in Example A1, except that the calcination temperature during the preparation of the first positive electrode material is 780°C and the calcination time is 10 h, and the calcination temperature during the preparation of the second positive electrode material is 780°C, resulting in different particle size parameters of the first positive electrode material and the second positive electrode material, see Table 1 for details.
[0100] The preparation method of the composite positive electrode material in Example A4 is basically the same as that in Example A1, except that the calcination temperature during the preparation of the first positive electrode material is 800° C., resulting in different particle size parameters of the first positive electrode material, as shown in Table 1 for details.
[0101] The preparation method of the composite positive electrode material in Example A5 is basically the same as that in Example A1, except that the calcination temperature during the preparation of the second positive electrode material is 700° C., resulting in different particle size parameters of the second positive electrode material, as shown in Table 1 for details.
[0102] The preparation method of the composite positive electrode material in Example A6 is basically the same as that in Example A1, except that the calcination temperature during the preparation of the second positive electrode material is 850° C., resulting in different particle size parameters of the second positive electrode material, as shown in Table 1 for details.
[0103] The preparation method of the composite positive electrode material in Example A7 is basically the same as that in Example A1, except that the calcination temperature during the preparation of the second positive electrode material is 800° C., resulting in different particle size parameters of the second positive electrode material, as shown in Table 1 for details.
[0104] The preparation method of the composite positive electrode material in Examples A8 to A10 is basically the same as that in Example A1, the only difference being that the mass content of the second positive electrode material and the first positive electrode material in the composite positive electrode material is different, as shown in Table 1 for details.
[0105] The preparation method of the composite positive electrode material in Examples A11 to A14 is basically the same as that in Example A1. The only difference is that the molar ratio of manganese and nickel elements is different during the preparation of the first positive electrode material, resulting in different values of x in the molecular formula of the first positive electrode material in the composite positive electrode material, see Table 1 for details.
[0106] The preparation method of the composite positive electrode material in Examples A15 to A16 is basically the same as that in Example A1. The only difference is that the molar ratio of nickel, cobalt and manganese elements is different during the preparation of the second positive electrode material, resulting in a different molecular formula of the second positive electrode material in the composite positive electrode material, as shown in Table 2 for details.
[0107] The preparation method of the composite positive electrode material in Example A17 is basically the same as that in Example A1, except that the magnesium content in the preparation process of the first positive electrode material, the tungsten content and the strontium content in the preparation process of the second positive electrode material are different, as shown in Table 2 for details.
[0108] The preparation method of the composite positive electrode material in Example A18 is basically the same as that in Example A9, except that the magnesium content in the preparation process of the first positive electrode material, the tungsten content in the preparation process of the second positive electrode material, and the strontium content are different, as shown in Table 2 for details.
[0109] The preparation method of the composite positive electrode material in Example A19 is basically the same as that in Example A10, except that the magnesium content in the preparation process of the first positive electrode material, the tungsten content in the preparation process of the second positive electrode material, and the strontium content are different, as shown in Table 2 for details.
[0110] Example A20
[0111] The preparation method of the composite positive electrode material provided in this embodiment is the same as that of the first positive electrode material in embodiment A1, except that the second positive electrode material is different. The second positive electrode material in this embodiment includes a molecular formula of Li(Ni 0.89 Co 0.05 Mn 0.05 Al 0.01 )O2) nickel-cobalt-manganese-aluminum quaternary positive electrode material, further comprising a second coating layer disposed on the surface of the nickel-cobalt-manganese-aluminum quaternary positive electrode material, the second coating layer comprising tungsten oxide and strontium oxide, and the preparation method thereof is as follows:
[0112] The nickel source (nickel hydroxide), cobalt source (cobalt trioxide), manganese source (manganese chloride), and aluminum source (aluminum oxide) are weighed according to the element molar ratio of Ni:Co:Mn:Al=89:5:5:1, and the lithium source (lithium hydroxide) is weighed according to the element molar ratio of Li:(Mn+Co+Ni)=1:1, and the above materials are mixed evenly to form a nickel-cobalt-manganese-lithium precursor; high-purity tungsten oxide and strontium oxide powders are accurately weighed according to the mass content of tungsten element and strontium element in the second positive electrode material being 0.1% and 0.05%, respectively, and then the high-purity tungsten oxide and strontium oxide powders are evenly mixed with the precursor; the temperature is raised to 750°C at a heating rate of 2°C / min in an oxygen atmosphere, kept warm for 12 hours, and calcined. The calcined product is ground (ball mill, speed 400r / min, time 120min) and classified (800-mesh sieve for classification) to obtain the first positive electrode material with the required particle size distribution.
[0113] In Comparative Example A1, only the first positive electrode material is used as the positive electrode material, and its preparation method is the same as that of Example A1.
[0114] In Comparative Example A2, only the second positive electrode material is used as the positive electrode material, and its preparation method is the same as that of Example A1.
[0115] The preparation method of the composite positive electrode material in Comparative Example A3 is basically the same as that in Example A1, except that the calcination temperature during the preparation of the first positive electrode material is 600° C., resulting in different particle size parameters of the first positive electrode material, as shown in Table 1 for details.
[0116] The preparation method of the composite positive electrode material in Comparative Example A4 is basically the same as that in Example A1, except that the calcination temperature during the preparation of the first positive electrode material is 900° C., resulting in different particle size parameters of the first positive electrode material, as shown in Table 1 for details.
[0117] The preparation method of the composite positive electrode material in Comparative Example A5 is basically the same as that in Example A1, except that the calcination temperature during the preparation of the second positive electrode material is 900° C., resulting in different particle size parameters of the second positive electrode material, as shown in Table 1 for details.
[0118] The preparation method of the composite positive electrode material in Comparative Example A6 is basically the same as that in Example A1, except that the calcination temperature during the preparation of the second positive electrode material is 630° C., resulting in different particle size parameters of the second positive electrode material, as shown in Table 1 for details.
[0119] Example B1
[0120] The lithium-ion secondary battery provided in this embodiment is prepared by the following method:
[0121] Step 1: Prepare the positive electrode
[0122] The composite positive electrode material prepared in Example A1, a conductive agent (carbon nanotubes and conductive carbon black in a mass ratio of 1:2), and a binder (polyvinylidene fluoride: PVDF) were dispersed in N-methylpyrrolidone in a mass ratio of 96%:2%:2% to obtain a uniform positive electrode slurry with a solid content of 70%. After adding 0.01% by mass of an additive (maleic acid) and mixing evenly, the positive electrode slurry was evenly coated on the surface of an aluminum foil (the aluminum foil used had a tensile strength of 320 MPa, a surface roughness of 1.3 μm, and a thickness of 10 μm), and a positive electrode sheet (with a compaction density of 3.3 g / cm 3 ).
[0123] Step 2: Prepare the negative electrode
[0124] The negative electrode active material graphite, the binder styrene butadiene rubber (SBR), the thickener carboxymethyl cellulose (CMC) and the conductive carbon black are dispersed in deionized water in a mass ratio of 96%:1.5%:1%:1.5% to obtain a uniform negative electrode slurry with a solid content of 45%. The negative electrode slurry is evenly coated on the surface of a copper foil, and a negative electrode sheet is obtained after drying and rolling.
[0125] Step 3: Battery Preparation
[0126] The positive electrode sheet prepared in the first step, the separator (with a total thickness of 10 μm, a polypropylene-polyethylene film as the substrate, an aluminum oxide as the ceramic layer, and a polyvinylidene fluoride (PVDF) as the coating layer, and the thicknesses of the coating layer, ceramic layer, substrate, and coating layer from top to bottom are 0.5 μm, 2 μm, 7 μm, and 0.5 μm, respectively), and the negative electrode sheet prepared in the second step are stacked in order, ensuring that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an aluminum-plastic film shell, and an electrolyte (lithium hexafluorophosphate dissolved in a mixed solution of propylene carbonate (PC), dimethyl carbonate (DMC), and fluoroethylene carbonate (FEC) in a volume ratio of 20:75:5, wherein the concentration of lithium hexafluorophosphate is 1.2 mol / L) is injected into the dried bare battery cell, and a lithium-ion battery is obtained through vacuum packaging, standing, formation, shaping, and sorting.
[0127] The preparation methods of the lithium-ion secondary batteries in Examples B2 to B20 are similar to those in Example B1, with the only difference being that the positive electrode sheets are prepared using the composite positive electrode materials prepared in Examples A2 to A20 of the present application instead of the composite positive electrode material prepared in Example A1.
[0128] The preparation method of the lithium ion secondary battery in Example B21 is basically the same as that in Example B1, except that aluminum foil with a tensile strength of 160 MPa, a surface roughness of 1.1 μm, and a thickness of 10 μm is used to prepare the positive electrode.
[0129] The preparation method of the lithium-ion secondary battery in Example B22 is basically the same as that in Example B1, except that aluminum foil with a tensile strength of 240 MPa, a surface roughness of 1.2 μm, and a thickness of 10 μm is used to prepare the positive electrode.
[0130] The preparation methods of the lithium-ion secondary batteries in Examples B23 to B24 are basically the same as those in Example B1, with the only difference being the thickness of the paste layer on one side. See Table 3 for details.
[0131] The preparation method of the lithium ion secondary battery in Example B25 is basically the same as that in Example B1, except that the compaction density is adjusted to 3.4 g / cm 3 , resulting in different porosity of the positive electrode sheet, see Table 3 for details.
[0132] The preparation method of the lithium ion secondary battery in Example B26 is basically the same as that in Example B1, except that the compaction density is adjusted to 3.2 g / cm 3 , resulting in different porosity of the positive electrode sheet, see Table 3 for details.
[0133] The preparation methods of the lithium-ion secondary batteries in Comparative Examples B1 to B6 are similar to those in Example B1, with the only difference being that the positive electrode sheets are prepared using the positive electrode materials prepared in Comparative Examples A1 to A6 of the present application, respectively.
[0134] Table 1 Structural parameters of composite cathode materials
[0135]
[0136]
[0137] Table 2 Structural parameters of composite cathode materials
[0138]
[0139]
[0140] “ / ” means it does not exist.
[0141] Test Case
[0142] 1. Positive electrode sheet resistance, resistivity, peel strength, porosity, and paste layer thickness test
[0143] Surface resistance: The rolled positive electrode sheet was cut into a rectangular size of approximately 5 cm × 10 cm and placed between the two electrodes of the membrane resistance meter. The test pressure was set to 0.4t and the holding time was 3s on the MRMS software. The test was started and the resistance data of the positive electrode sheet was read. Three positions were randomly selected for testing on each membrane. The test results are shown in Table 3.
[0144] Resistivity: The rolled positive electrode sheet was cut into a rectangular shape of approximately 5 cm × 10 cm and placed on the sample stage of a multifunctional digital four-probe tester. The measurement parameters were set and the test was conducted for 5 seconds. The resistivity data of the positive electrode sheet was read. Three locations on each electrode sheet were randomly selected for single-sided and double-sided resistivity testing. The test results are shown in Table 3.
[0145] Peel strength: The test equipment is a tensile testing machine. Cut the rolled positive electrode sheet into 25mm widths. Prepare a flat thin steel plate and apply a strip of double-sided tape to its center. Attach the electrode to the double-sided tape, ensuring that the electrode and the tape are perfectly matched to avoid test errors. Insert the steel plate with the fixed electrode into the lower fixture of the tensile testing machine and fix it vertically. Clamp the unattached electrode in the upper fixture at a 90° angle to the electrode in the lower fixture. Set parameters such as test width, peel length, and peel speed on the tensile testing machine. Start the test program. The tensile testing machine will apply tensile force according to the set parameters and record the force changes during the peeling process. After the test is completed, the peel strength curve and average value data will be obtained. The test results are shown in Table 3.
[0146] Porosity determination method for positive electrode sheets: Based on Bohr's law for inert gases (such as helium) under certain conditions, a true density meter is used to accurately measure the true volume of the sample, thereby obtaining its porosity. Porosity can be calculated using the following formula: Porosity = (Apparent Volume - True Volume) / Apparent Volume × 100%. Test results are shown in Table 3.
[0147] Thickness of the paste layer: Use a micrometer to measure the electrode after rolling. Randomly select 10 positions on the electrode for testing. After the test, take the average of the 10 data as the thickness H0 of the electrode. Use the micrometer to measure the thickness H2 of the current collector before coating according to the above method. The thickness of the coating H = H0-H2. The test results are shown in Table 3.
[0148] 2. Battery capacity, battery internal resistance, average discharge voltage, and volume energy density test
[0149] ① Charge the lithium-ion battery to full capacity at 25°C with constant current and constant voltage (charge at 0.5C to 4.2V, then charge at constant voltage to 0.05C and then discharge at 0.2C to 3V. The discharged capacity is recorded as the battery capacity.
[0150] ② Charge the lithium-ion battery to 30% SOC at 25°C (0.5C) and test the internal resistance of the battery using an internal resistance tester;
[0151] ③ Charge the lithium-ion battery to full capacity at 25°C at a constant current (0.5C charging to 4.2V, then constant voltage charging to 0.05C cutoff), then discharge it to 3V at 0.2C. The discharged capacity is recorded as the battery capacity, and the discharged energy is recorded as the discharge energy. Calculate the average discharge voltage = discharge energy / discharge capacity;
[0152] ③ Charge the lithium-ion battery to 30% SOC at 25°C and use 600g PPG to test the battery thickness;
[0153] ④ Calculate the volume energy density = battery capacity * average discharge voltage / battery length / width / thickness; The above test results are shown in Table 4.
[0154] 3. Cycle performance test
[0155] The lithium-ion battery was subjected to a 1C / 5C cycle test at 35°C, specifically 1C charging to 4.2V, 0.05C cut-off, 5C discharge to 3V, repeated 500 times, and 0.2C charging to 4.2V, 0.05C cut-off, 0.2C discharge to 3V every 100 cycles. The retention rate and expansion rate of the test cycle were tested for 500 cycles. The test results are shown in Table 5, and the cycle retention rate curve is shown in Figure 1 500-week capacity retention rate = remaining capacity / initial capacity * 100%, thickness expansion rate = (final thickness - initial thickness) / initial thickness * 100%.
[0156] 4. Overcharge performance test
[0157] Lithium-ion batteries were subjected to 2C-4.8V and 2C-5V overcharge tests at 25°C. After discharging the batteries at 0.5C, they were charged at a 2C overcharge current to 4.8V and 5V, respectively, before switching to a constant voltage for 7 hours. Batteries were considered to have passed if they did not catch fire or explode. Each group tested 20 batteries, and the number of batteries that passed the test was recorded. The test results are shown in Table 5.
[0158] 5. Furnace temperature test
[0159] Lithium-ion batteries were charged at 25°C at 0.5C to 4.2V, then charged at a constant voltage to 0.05C. The batteries were then placed in an incubator, heated at a rate of 5°C / min to 130°C ± 2°C and 140°C ± 2°C, and maintained at this temperature for 60 minutes. Batteries were considered to have passed if they did not catch fire or explode. Each group tested 20 batteries, and the number of batteries that passed the test was recorded. The test results are shown in Table 5.
[0160] Please see Table 3-Table 5 for the above test results.
[0161] As can be seen from Table 3, with the increase in the mixing ratio of the first positive electrode material, the surface resistance and resistivity of the electrode sheet both increase to a certain extent, indicating that the conductivity of the first positive electrode material is higher than that of the second positive electrode material. The increase in the resistivity and surface resistance of the electrode sheet can reduce the local current density inside the battery, thereby reducing the heat generated during battery operation. At the same time, it can improve the high voltage resistance of the positive electrode sheet, reduce the voltage overshoot problem that may occur during battery charging and discharging, and help improve the safety and stability of the battery.
[0162] Table 3 Structure and performance parameters of positive electrode
[0163]
[0164] Table 4 Electrical properties of lithium-ion secondary batteries
[0165]
[0166]
[0167]
[0168] Table 5 Cycling performance and safety of lithium-ion secondary batteries
[0169]
[0170]
[0171]
[0172]
[0173] The data in Table 4 shows that as the proportion of the first positive electrode material increases, the internal resistance of the battery increases slightly. The increase in internal resistance is mainly caused by the increase in the surface resistance of the electrode sheet. The increase in battery internal resistance can slow down the chemical reaction rate in the battery and reduce the dissolution rate of the positive and negative electrode materials in the electrolyte, thereby extending the cycle life of the battery. Secondly, as the proportion of the first positive electrode material increases, due to the use of the second positive electrode material with the above characteristics and the first positive electrode material, even if the mixing ratio of the first positive electrode material is increased to 50%, the compaction density of the positive electrode sheet can still reach 3.25g / cm 3 As can be seen from Example A9, the thickness of the battery prepared by mixing 50% of the first positive electrode material increases slightly, while the thickness of the battery prepared by Comparative Example A1 is greatly increased due to the use of 100% of the first positive electrode material as the positive electrode material, and the volume energy density is significantly lost; in addition, as the mixing ratio of the first positive electrode material increases, the average discharge voltage of the battery continues to increase, such as Figure 1 As shown, even after 50% of the first positive electrode material is blended, the battery thickness increases, but the energy density of the battery is not lost due to the higher average voltage.
[0174] Table 5 and Figure 2 The data shows that for the battery of Comparative Example B1, which only uses the first positive electrode material as the positive electrode active material, manganese is continuously dissolved due to the Jahn-Taller effect. After only 350 cycles at a temperature of 35 degrees, Comparative Example B1 swells and plummets, with a retention rate as low as 15.3% and an expansion rate as high as 20.8%. However, after 500 cycles of the battery of the composite positive electrode material used in the present invention, the retention rate is ≥90% and the expansion rate is ≤10%, indicating that by mixing the first positive electrode material and the second positive electrode material, the defects of the first positive electrode material are compensated, the structural stability of the material is improved, the dissolution rate of manganese is reduced, and its cycle stability is improved.
[0175] The data in Table 5 show that the safety performance of the hybrid positive electrode using the comparative example B2 with a purer second positive electrode material has been significantly improved. Since the amount of oxygen released by the first positive electrode material during charging and discharging is relatively small, the hybrid positive electrode has a lower oxygen release rate compared to high-nickel materials. This reduces the possibility of gas accumulation inside the battery, thereby reducing the risk of internal gas explosion in the battery. In addition, the first positive electrode material mixed with the second positive electrode material has better overcharge resistance than traditional nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) materials under high-voltage charging conditions. This means that during charging, even if the battery is charged to a higher voltage, the first positive electrode material mixed with the second positive electrode material can maintain the stability of the material structure, reducing safety risks during charging.
[0176] The data in Table 5 show that the batteries of Examples B1-B26 using the composite positive electrode material of the present invention have significantly improved electrochemical performance, cycle stability, and safety performance compared to Comparative Examples B3-B6, in which the ratio of Dv1 of the first positive electrode material to Dv2 of the second positive electrode material is not within the scope protected by the present invention. In particular, Example A10 and Comparative Example A2 have comparable safety performance, both being able to pass 2C-5V overcharge and 140°C furnace temperature.
[0177] Obviously, the above embodiments are merely examples for clarity of explanation and are not intended to limit the implementation methods. Those skilled in the art will appreciate that other variations or modifications can be made based on the above description. It is not necessary and impossible to enumerate all implementation methods here. Obvious variations or modifications arising therefrom remain within the scope of protection of this application.
Claims
1. A composite positive electrode material, characterized in that: The composite positive electrode material includes a first positive electrode material and a second positive electrode material, the first positive electrode material includes one or more of lithium manganese oxide and nickel-doped lithium manganese oxide materials, and the second positive electrode material includes one or more of nickel-cobalt-manganese ternary positive electrode materials and nickel-cobalt-manganese-aluminum quaternary positive electrode materials; The composite positive electrode material satisfies the following relationship: 1.35≤Dv1 / Dv2≤14.29; Among them, Dv1=Dv1(100)*Dv1(99) / Dv1(50), Dv2=Dv2(100)*Dv2(99) / Dv2(50), Dv1(50), Dv1(99), Dv1(100) are the particle sizes corresponding to the cumulative particle size distribution percentages of the first positive electrode material reaching 50%, 99%, and 100%, respectively; Dv2(50), Dv2(99), Dv2(100) are the particle sizes corresponding to the cumulative particle size distribution percentages of the second positive electrode material reaching 50%, 99%, and 100%, respectively.
2. The composite positive electrode material according to claim 1, characterized in that 5μm≤Dv1(50)≤15μm, 30μm≤Dv1(100)≤50μm, 20μm≤Dv1(99)≤40μm, 80μm≤Dv1≤230μm; and / or, 1μm≤Dv2(50)≤5.2μm, 5μm≤Dv2(100)≤20μm, 5μm≤Dv2(99)≤15μm, 15μm≤Dv2≤60μm.
3. The composite positive electrode material according to claim 1 or 2, characterized in that: The composite positive electrode material satisfies one or two of the following AB: A. The first positive electrode material has the following molecular formula: LiMn 2-x Ni x O4, wherein 0≤x≤0.3; preferably, 0.1≤x≤0.2; B. The second positive electrode material has the following molecular formula: Li(Ni x Co y Mn z Al m )O2, where 0.85 ≤ x < 1, 0 < y < 0.1, 0 < z < 0.1, 0 ≤ m < 0.1, and x + y + z + m = 1; preferably, 0.88 ≤ x < 1, 0 < y < 0.05, 0 < z < 0.05, 0 ≤ m < 0.02, and x + y + z + m = 1.
4. The composite positive electrode material according to any one of claims 1 to 3, characterized in that: The first positive electrode material accounts for 10%-90% of the composite positive electrode material by mass, and the second positive electrode material accounts for 10%-90% of the composite positive electrode material by mass; and / or, the first positive electrode material contains single crystal particles; and / or, the second positive electrode material contains single crystal particles.
5. The composite positive electrode material according to any one of claims 1 to 4, characterized in that: The composite positive electrode material satisfies one or two of the following ab: a. A first coating layer is provided on the surface of the first positive electrode material, the first coating layer includes a first coating element, and the first coating element includes magnesium; b. A second coating layer is disposed on the surface of the second positive electrode material. The second coating layer includes a second coating element. The second coating element includes at least one of tungsten and strontium.
6. The composite positive electrode material according to claim 5, characterized in that: The composite positive electrode material also satisfies the following relationship: 0.33≤A / (B+C)≤50; Among them, A is the mass content of the first coating element based on the mass of the first positive electrode material; B is the mass content of the tungsten element based on the mass of the second positive electrode material; C is the mass content of the strontium element based on the mass of the second positive electrode material; 0.1%≤A≤1%, 0.01%≤B≤0.2%, 0.01%≤C≤0.1%.
7. The composite positive electrode material according to any one of claims 1 to 6, characterized in that: In the XRD diffraction pattern of the second positive electrode material, the peak intensity I(003) of the crystal plane (003) and the peak intensity I(104) of the crystal plane (104) satisfy: I(003) / I(104)≥1.2; And / or, in the XRD diffraction pattern of the second positive electrode material, the peak intensity I(101) of crystal plane (101), the peak intensity I(006) of crystal plane (006) and the peak intensity I(012) of crystal plane (012) satisfy: (I(006)+I(012)) / I(101)≤0.
5.
8. A positive electrode sheet, characterized in that: It comprises a current collector and a paste layer disposed on the current collector, wherein the paste layer comprises the composite positive electrode material according to any one of claims 1 to 7; Optionally, the thickness of the current collector is 8-16 μm, and the thickness of a single surface of the paste layer is 10-100 μm; Optionally, the resistivity of the positive electrode plate is 0.2-5KΩ·cm, and the surface resistance is 20-600mΩ; Optionally, the peel strength of the positive electrode sheet is 0.01-0.2 kgf; Optionally, the porosity of the positive electrode plate is 20%-40%.
9. The positive electrode sheet according to claim 8, characterized in that: The current collector is an aluminum foil; preferably, the tensile strength of the aluminum foil is ≥150Mpa, the surface roughness is 0.1-1.5μm, and the thickness of the aluminum foil is 8-16μm.
10. A lithium ion secondary battery, comprising the positive electrode sheet according to claim 8 or 9; and also comprising an electrolyte; Preferably, the electrolyte comprises a lithium salt, an organic solvent and an additive; More preferably, the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorooxalatoborate), and lithium bis(fluorosulfonylimide); More preferably, the organic solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate; More preferably, the additive includes one or more of vinylene carbonate, fluoroethylene carbonate, vinylethylene carbonate and 1,3-propane sultone.
Citation Information
Cited By
Positive plate, lithium ion battery and electric device
CN121331781A
